Intrinsic properties of osteomalacia bone evaluated by nanoindentation and FTIRM analysis. (5th March 2021) - Hadjab, I.; Farlay, D.; Crozier, P.; Douillard, T.; Boivin, G.; Chevalier, J.; Meille, S.; Follet, H.
Abstract: Osteomalacia is a pathological bone condition consisting in a deficient primary mineralization of the matrix, leading to an accumulation of osteoid tissue and reduced bone mechanical strength. The amounts, properties and organization of bone constituents at tissue level, are known to influence its mechanical properties. It is then important to investigate the relationship between mechanical behavior and tissue composition at this scale in order to provide a better understanding of bone fragility mechanisms associates with this pathology. Our purpose was to analyze the links between ultra-structural properties and the mechanical behavior of this pathological bone tissue (osteomalacia) at tissue level (mineral and osteoid separately, or global). Four bone biopsies were taken from patients with osteomalacia, and subsequently embedded, sectioned, and polished. Then nanoindentation tests were performed to determine local elastic modulus E, contact hardness Hc and true hardness H for both mineralized and organic bone phases and for the global bone. The creep of the bone was also studied using a special indentation procedure in order to assess visco-elasto-plastic (creep) bone behavior. This allowed a detailed study of the rheological models adapted to the bone and to calculate the parameters associated to a Burgers model. Ultra-structural parameters were measured by Fourier Transform InfraRed Microspectroscopy (FTIRM) on the same position as the indents. The use of rheological models confirmed a significant contribution from the organic phase on the viscous character of bone tissue. The elastic E and the elasto-plastic Hc deformation were correlated to both collagen maturity and Mineral/Matrix. The pure plastic deformation H was only correlated to the mineral phase. Our data show that mineral phase greatly affects mechanical variables (moduli and viscosities) and that organic phase (as illustrated in osteoid tissue) may play an important role in the creep behavior of bone. In conclusion, this study brings mechanical and physicochemical values for osteoid and mineral phases.